A Study of Prognosis, Outcome, and Changing Tendency of Hospitalized AMI Patients in Beijing Third-Grade A-Level Traditional Chinese Medicine Hospitals from 1999 to 2008. (22nd March 2012) - Shang, Ju-Ju; Shi, Hui; Zhou, Qi; Gao, Wei; Liu, Hong-xu
Abstract : Objectives . To survey and analyse the prognosis, outcome, and changing tendency of the Acute Myocardial Infarction (AMI) patients in Beijing third-grade A-level Traditional Chinese Medicine (TCM) hospitals. Methods . We collected the clinical datum of hospitalized AMI patients in Beijing 6 TCM hospitals from January 1999 to December 2008 and then analysed the clinical datum. Results . (1) The mean age of patients had showed a slowly rising tendency during this ten years. The patients who had previous history of cerebrovascular diseasea and multiple comorbidities had increased year by year. (2) The rate of reperfusion therapy, revascularization and standardized using of drug, and usage of TCM of AMI patients presented a significant increasing tendency in these hospitals. (3) The proportion of AMI patients combined with cardiac arrhythmia and heart failure had decreased significantly. (4) The AMI mortality presented a decreasing tendency in 10 years. Conclusions . The AMI patients in Beijing TCM hospitals had their own unique clinical features, and it can improve their prognosis by combined therapy of Western Medicine and Traditional Chinese Medicine.